Islamic Economic Development Strategy According to Adiwarman Azwar Karim - Musa (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2022)
Adiwarman Azwar Karim is one of the experts in the field of Islamic economics so that he is included in the list of fundamentalist Muslim thinkers. His contribution to the development of Islamic banking and economics in Indonesia is not only as a practitioner, but also as an academic. The method in this study is a qualitative literature review. The Islamic economic development strategy that he designed has three levels, namely Islamic economic theory, Islamic economic system, and Muslim economy. The three levels refer to the components of language, discourse, main actors, and arguments related to the development of Islamic economics. When one of these levels is not achieved, it will not result in the establishment of Islam in the economic field. A strong Islamic economic theory without the implementation of the system will not have an impact on economic life.